Analyzing the Influence of Demographic Factors on Consumer Preferences in the Tourism Industry in Bali - Santi Diwyarthi, Ni Desak Made; Pratama, I Wayan Adi; Jata, I Wayan; Mas Wiartha, Nyoman Gede; Darmiati, Made (West Science Social and Humanities Studies, 2024)
This research investigates the influence of demographic factors on consumer preferences within the tourism industry in Bali. 250 tourists examined their accommodation choices, activity preferences, and overall satisfaction. The study employs Structural Equation Modeling with Partial Least Squares (SEM-PLS) to analyze the data. Results reveal nuanced patterns: younger tourists favor budget accommodations, older tourists opt for luxury, and higher-income individuals prefer upscale options. Gender and education impact preferences, emphasizing the need for tailored strategies. The measurement model assessment confirms the reliability and validity of the constructs. Findings contribute to understanding Bali's tourism dynamics, guiding businesses and policymakers in optimizing offerings for diverse demographic segments.